2021
DOI: 10.1101/2021.01.13.21249757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Network-derived perfusion maps: a Model-free approach to computed tomography perfusion in patients with acute ischemic stroke

Abstract: PurposeIn this study we investigate whether a Convolutional Neural Network (CNN) can generate clinically relevant parametric maps from CT perfusion data in a clinical setting of patients with acute ischemic stroke.MethodsTraining of the CNN was done on a subset of 100 perfusion data, while 15 samples were used as validation. All the data used for the training/validation of the network and to generate ground truth (GT) maps, using a state-of-the-art deconvolution-algorithm, were previously pre-processed using a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The second class is to directly estimate HPMs from the low-dose CTP images. For example, Gava et al investigated the potential of the neural networks in HPM estimation from the measured CCTP data, and found that the neural networks can produce clinically relevant HPMs (Gava et al 2021). Robben et al presented a neural network and a data augmentation approach to estimate HPMs directly from the low-dose CTP measurements (Robben and Suetens 2018).…”
Section: Deep Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second class is to directly estimate HPMs from the low-dose CTP images. For example, Gava et al investigated the potential of the neural networks in HPM estimation from the measured CCTP data, and found that the neural networks can produce clinically relevant HPMs (Gava et al 2021). Robben et al presented a neural network and a data augmentation approach to estimate HPMs directly from the low-dose CTP measurements (Robben and Suetens 2018).…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Clrigues et al proposed a patch based asymmetrical residual encoder-decoder network for infarct core segmentation in the CT/CTP images and accurately predicted infarct core size and location(Clérigues et al 2019). Gava et al constructed a U-Net based network structure to segment infarct core and penumbra with high Dice and Pearson correlation coefficients across lesion volumes(Gava et al 2021). Tao proposed a end-to-end generative model-based segmentation network to segment infarct core and penumbra regions(Tao 2014).…”
mentioning
confidence: 99%
“…Indeed, DL allows the extraction of information and features that are relatively insensitive to noise, misalignment and variance. Gava et al [10] shows whether a properly trained Convolutional Neural Network (CNN), based on a U-Net-like structure, on a pre-processed dataset of CTP images, can generate clinically relevant parametric maps of CBV, CBF and time to peak TTP.…”
Section: Methodsmentioning
confidence: 99%
“…This particular neural network architecture has been originally developed for image segmentation: however, it proved to be effective also to solve other image generation tasks. For our purpose, we reproduce the suggested modifications [10] at the architectural level to fit the problem. For segmentation tasks, a common state-of-the-art choice is to use max-pooling layers for sub-sampling.…”
Section: Network Architecturementioning
confidence: 99%
See 1 more Smart Citation